The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1021/acs.jpcb.7b05015
|View full text |Cite
|
Sign up to set email alerts
|

Local Degradation Mechanisms by Tarnishing of Protected Silver Mirror Layers Studied by Combined Surface Analysis

Abstract: In this work, we addressed the local degradation mechanisms limiting the prelaunch environmental durability of thin-layered silver stacks for demanding space mirror applications. Local initiation and propagation of tarnishing were studied by combined surface and interface analysis on model stack samples consisting of thin silver layers supported on lightweight SiC substrates and protected by thin SiO overcoats, deposited by cathodic magnetron sputtering and submitted to accelerated aging in gaseous HS. The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 70 publications
7
9
0
Order By: Relevance
“…They confirmed that the surface porosity characterizing the SiC substrate and originating from the material production process is suppressed by the CVD surface treatment like specified by the provider. On the SiC substrate ( Figure 1(a,b)), the lateral dimensions (0.5-6 µm), depth (0.05-0.4 µm) and density (~1.6×10 6 cm -2 ) of the surface pores remain essentially unchanged after deposition of the stacks, showing that the pores remain incompletely filled and that the surface still exhibits high aspect ratio topographic sites as discussed previously [35]. On the SiC+CVD substrate (Figure 1(d…”
Section: Methodssupporting
confidence: 57%
See 4 more Smart Citations
“…They confirmed that the surface porosity characterizing the SiC substrate and originating from the material production process is suppressed by the CVD surface treatment like specified by the provider. On the SiC substrate ( Figure 1(a,b)), the lateral dimensions (0.5-6 µm), depth (0.05-0.4 µm) and density (~1.6×10 6 cm -2 ) of the surface pores remain essentially unchanged after deposition of the stacks, showing that the pores remain incompletely filled and that the surface still exhibits high aspect ratio topographic sites as discussed previously [35]. On the SiC+CVD substrate (Figure 1(d…”
Section: Methodssupporting
confidence: 57%
“…Accelerated atmospheric aging was performed in gaseous H2S selected as most corrosive indoor atmospheric agent of silver. The accelerated aging tests were performed at 1000 mbar H2S and 75°C for 24, 48 and 96 h, like previously described [35]. The sulfurized samples were transferred through air for surface analysis.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations